OPTIMIZATION OF QARD FINANCING IN MICRO BUSINESS DEVELOPMENT AT BWM AL-ANSHOR PEDULI AMBON - Holle, Mohammad H; Warang, Japri Yusrifal (AT-TIJARAH: Jurnal Penelitian Keuangan dan Perbankan Syariah, 2024)
The research aims to determine the optimization of qard financing in the development of micro businesses at the Al-Anshor Peduli Ambon Micro Waqf Bank. This research uses field studies with a case study approach. The data collection technique uses observation, interviews and documentation. Data is collected then processed and analyzed using a descriptive-qualitative mindset with a deductive nature. Research results: 1. Optimization of qard financing at the Al-Anshor Peduli Ambon Micro Waqf Bank was carried out in groups consisting of 15-25 members. These business actors then apply for financing in the form of loans with a value of IDR 1 million up to a maximum limit of IDR 3 million without any collateral or collateral. This financing is then tied into a contract or financing agreement called qard. To overcome bottlenecks, member financing installments are carried out jointly. 2. Qard financing at the Al-Anshor Peduli Ambon Micro Waqf Bank has had a positive impact on business development for micro business actors who take out this financing. Either to add working capital to cover the lack of funds needed by customers or to start a business or in order to develop the business of micro business actors in the city of Ambon using qard contracts.